Analisis Validitas dan Reliabilitas Soal Pilihan Ganda dengan Menggunakan Software Anates pada Mata Pelajaran Perpajakan - Augustia, Amanda Diskafrida; Agustia, Charisma Nurochmatiana; Azzahra, Divanida; Hakim, Luqman; Pratiwi, Vivi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study discusses the importance of analyzing the quality of question items as an evaluation step in education to ensure the accuracy of student learning outcome assessment. The focus of this research is on the subject of Tax Administration class XI majoring in Accounting at SMKN 4 Surabaya, using Anates software version 4. The method used was descriptive quantitative with 25 students and 15 HOT-based multiple-choice questions. The analysis includes reliability, validity, discriminating power, level of difficulty, and quality of the trickster. Reliability measures the consistency of test results, while validity indicates the extent to which the question is in accordance with the learning objectives. The ability to discriminate assesses the ability of questions in grouping high- and low-ability students, while the level of difficulty reflects the proportion of students who are able to answer correctly. Good quality of tricksters contributes to the discriminating power and difficulty level of the questions. The results of this study emphasize the importance of quality evaluation instruments to improve learning effectiveness, with the support of technology such as Anates to facilitate problem analysis.